2001
DOI: 10.1177/070674370104601005
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Epidemiology of Attention-Deficit Hyperactivity Disorder: Screening Method and Pilot Results

Abstract: These data suggest that the DSM-IV prevalence of ADHD has been substantially underestimated, although the true prevalence in this population may be less than the 16% estimated here. Population-based studies of ADHD are feasible and may provide important information about practice and treatment patterns in community settings, as well as a broader understanding of the etiology and life course of this common disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 36 publications
5
59
1
2
Order By: Relevance
“…Differences in prevalence between different racial and ethnic groups have not been adequately examined in population-based studies; additional research is needed. Preliminary data from a North Carolina study suggest little difference in the history of ADHD diagnosis between African-American and white children but more substantial racial differences in medication treatment patterns [Rowland et al, 2001;. In that study, 8% of white elementary school children were being treated for ADHD with medication compared to 5% of African-American children and 2% of Hispanic children [Rowland et al, 2002].…”
Section: Prevalence Of Adhdmentioning
confidence: 89%
See 1 more Smart Citation
“…Differences in prevalence between different racial and ethnic groups have not been adequately examined in population-based studies; additional research is needed. Preliminary data from a North Carolina study suggest little difference in the history of ADHD diagnosis between African-American and white children but more substantial racial differences in medication treatment patterns [Rowland et al, 2001;. In that study, 8% of white elementary school children were being treated for ADHD with medication compared to 5% of African-American children and 2% of Hispanic children [Rowland et al, 2002].…”
Section: Prevalence Of Adhdmentioning
confidence: 89%
“…This may represent only part of the problem because medication treatment is usually less effective in real world settings than it is in clinical trials where compliance and side-effects are carefully monitored. For example, a North Carolina study reported that over a third of the children receiving ADHD medication treatment showed six or more symptoms of ADHD and impairment at school [Rowland et al, 2001]. Further, medication alone often does not normalize behavior.…”
Section: Adhd As a Public Health Concernmentioning
confidence: 99%
“…Although the DSM IV age criterion to establish the diagnosis is 7 years, new studies are reporting patients with diagnosis done after 7 years, in particular those cases exhibiting the inattentive type. 72 Associated limitations involve the presence of comorbid and underlying conditions that mimic in part ADHD, especially in studies us- Modified from DSM IV. 22 ing rating scales or structured diagnostic interviews, rather than clinician-based semistructured interviews.…”
Section: Epidemiology Of Adhdmentioning
confidence: 99%
“…Consequently, reports of ADHD prevalence may provide estimates as wide as 2-18% [Rowland et al, 2001]. A large cohort study recently estimated the prevalence of 'definite' ADHD among US children to be 7.4%, but when 'probable' and 'questionable' cases were included the estimate became 16.0% [Barbaresi et al, 2002].…”
mentioning
confidence: 99%